PENGELOLAAN KOMUNIKASI PRIVASI REMAJA AKHIR KEPADA ORANG TUA MENGENAI HUBUNGN ROMANTIS MENUJU PERILAKU SEKSUAL - Martina, Rina; Pratiwi, Aprilyanti (Istek Widuri Jakarta, 2022)
The quality of the relationship between parents and children will be different in each family, including how to convey information will affect the relationship between parents and children. This study aims to analyze how a late teenager chooses and manages privacy boundaries to parents regarding sexual behavior. The theory used in this study is the Communication Privacy Management Theory (CPM), a theory that describes that every individual makes a choice about disclosing or not disclosing personal information, because every individual has the right to regulate access to their personal information. This study uses an interpretive paradigm with qualitative methods. The data collection technique in this research is semi-structured interview. Informants in this study were late teens in the city of Bogor. The results show that late teens can form private boundaries regarding the privacy realm of sexual behavior. Thus, late teens have a fairly high management of privacy communication to their parents, but in essence, late teens have a choice of positive expressions to their parents, and hide negative things such as sexual behavior. In self-disclosure, late teens tend to be closed to their parents regrading sexual behavior in their romantiv relationship because late teens have doubts, are refair of having an impact on their family relationship, bevause parents who have given trust to late teens and late teens also want to maintain their parents trust so they don’t disappointing. Whereas late teens are open to their parents about having a romantic relationship with their parents don’t forbid it.